Student Organisations as Epistemic Spaces for the Cultivation of Critical Awareness: A Study in the Philosophy of Science - Moch. Syakroni; Amanat Solikah; Adimas Setiawan (South Sulawesi Education Development (SSED), 2025)
This study aimed to understand both conceptually and empirically how student organisations functioned as epistemic spaces in fostering critical consciousness through the lens of the philosophy of science. The focus of the research encompassed three main dimensions: ontology, epistemology, and axiology. The study employed a descriptive qualitative approach, using data collection techniques such as in-depth interviews, activity observations, and documentation conducted at the IMM (Ikatan Mahasiswa Muhammadiyah) Commissariat of Muhammadiyah University of Surabaya. The findings revealed that, ontologically, the IMM Commissariat existed as a social entity that played an active role in the dynamics of campus and community life. Epistemologically, it served as a dialectical space for members to acquire and validate knowledge through cadre development, intellectual forums, and service activities. Axiologically, the IMM Commissariat implemented scientific and Islamic values in the form of concrete contributions through socially beneficial activities. This entire process cultivated members who not only thought critically but also possessed social awareness and moral integrity. Thus, the IMM Commissariat proved to be a relevant epistemic space in developing critical consciousness, both within the academic environment and in broader societal contexts.